A carbon paste electrode modified with bituminous coal for studying its sorption properties - Navrátilová, Zuzana (Univerzita Pardubice, 2011)
Sorption properties of bituminous coal sample were studied by means of voltammetry on the coal modified carbon paste electrode. Influence of the presence of alkylammonium cation and the temperature on the sorption of metals was studied and interpreted, too. An inhibition effect of hexadecylammonium bromide, as well as of the increasing temperature, was observed for three metals; namely, cadmium, lead, and copper.
Keywords: carbon paste electrode; modified carbon paste; coal; adsorption of metal ions